Peran Kepala Sekolah Dalam Meningkatkan Kompetensi Pedagogik Guru Di SD Negeri 1 Jeumpet Kabupaten Aceh Besar - Devi Fazrani Destya; Darnius Said; intan Safiah (Universitas Syiah Kuala, 2022)
The reason for the review was to decide the job of the chief in working on the educational capability of educators. The formulation of the issue in this study is the manner by which the job of the chief in working on the pedagogical capability of educators in SD Negeri 1 Jeumpet Aceh Besar Regency is. This study utilizes a subjective methodology with a descriptive kind of approach. The subjects of this review were the head and 3 study hall educators. The information assortment procedure utilized by the scientist was perception and interview strategies, which were handled with the information examination stages, to be specific, information decrease, information show, and information check. In light of the consequences of the review, it shows that the chief plays did the parts of teacher, chairman, administrator, boss, pioneer, trendsetter, and inspiration. The chief likewise remember educators for meetings, KKG, studios, and workshops as well as preparation stages to expand information and involvement with the growing experience in the homeroom. The chief behaviors are class visits, class perceptions, and gives or preparing satisfactory hardware to educators and understudy so that instructing and educational experience accomplishes objectives thus that the nature of the school increment and later the instructor's academic skill will likewise increment